2018
DOI: 10.1002/job.2319
|View full text |Cite
|
Sign up to set email alerts
|

Introducing changes at work: How voice behavior relates to management innovation

Abstract: This multistudy research examines the unit-level relationship between promotive voice behavior and management innovation. Study 1 utilizes multisource data from 62 work units and reports that willingness to discuss ideas mediates the unit-level relationship between promotive voice and management innovation. The results of Study 1 also show that the unit's available resources make the relationship stronger between promotive voice and willingness to discuss ideas. Study 2 employs a scenario-based design to const… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
78
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(87 citation statements)
references
References 109 publications
(224 reference statements)
2
78
0
4
Order By: Relevance
“…However, merely developing innovative ideas is not enough. As a subsequent step, employees' ideas can only turn into action when they are articulated (Guzman and Espejo 2018). Thus, the second cornerstone and final outcome of the present study is voice behavior, which reflects employees' willingness to make new suggestions and articulate ideas (LePine and Van Dyne 1998).…”
Section: Introductionmentioning
confidence: 82%
“…However, merely developing innovative ideas is not enough. As a subsequent step, employees' ideas can only turn into action when they are articulated (Guzman and Espejo 2018). Thus, the second cornerstone and final outcome of the present study is voice behavior, which reflects employees' willingness to make new suggestions and articulate ideas (LePine and Van Dyne 1998).…”
Section: Introductionmentioning
confidence: 82%
“…The articles by Guzman and Espejo () and Liang () investigate the connection between voice behavior and innovation at the team level. Guzman and Espejo () showed that team promotive voice behavior (expressing new ideas or suggestions for improving the overall functioning of their work unit or organization) predicted team members' willingness to express ideas, which then predicted team innovation. This positive indirect route was stronger when available resources were high rather than low.…”
Section: Articlesmentioning
confidence: 99%
“…The goal of this special issue is to deepen our understanding of the consequences of proactive behaviors by expanding the scope of outcomes, integrating them with work contexts, and adopting new methodologies. We are excited to present seven articles that cover a wide range of the consequences of proactive behaviors, including employee daily work outcomes (Cangiano, Parker, & Yeo, ), personal initiative training outcomes for entrepreneurs (Mensmann & Frese, ), social status (Weiss & Morrison, ), affective and well‐being consequences (Zacher, Schmitt, Jimmieson, & Rudolph, ), career success (Smale et al, ), and team innovation (Guzman & Espejo, ; Liang, ). Many of these studies have seriously considered social contexts at different levels, including the intra‐individual level (Cangiano et al, ), the team level (Guzman & Espejo, ; Liang, ), and the national cultural level (Smale et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Voice behavior is often considered to be significant in the organizations because nowadays organizations depend on innovative ideas and rapid response to grow in the ever-changing marketplaces and excessive competition (Guzman & Espejo, 2019;Liu, Zhu, & Yang, 2010;Edmondson, 1999;Morrison & Phelps, 1999). Voice behavior is defined as "proactively challenging the status quo and making constructive suggestions" (Van Dyne, Cummings, & McLean Parks, 1995, p. 266).…”
Section: Introductionmentioning
confidence: 99%